Hill paddy plough / Jasrio Liugan ... [et al.] - Liugan, Jasrio; Melulin, Sainah; Halledy, Zurhizainih; Abd Khalid, ‘Umairah (2021)
Hill paddy is widely grown small-scale by farmers mostly in Sabah and Sarawak. Hill paddy has special characteristics in terms of smell, colour, size and shape. The agronomic practices of hill paddy are not the same as those done to paddy fields. This is due to geographical factors when the location of cultivation of hill slope paddy seeds makes it difficult for residents to use machinery compared to flat border areas such as paddy field. It is a major requirement for farmers to acquire practical tool that make holes in the soil to insert paddy into the soil and to plant paddy. So, we introduce an innovative tool called the Hill Paddy Plough to lower labour consumption. It can assist farmers to complete the task at the hilly areas with lesser time. In the future, improvements will be made and brought significant efficiency involving time and energy usage of all farmers.